2015
DOI: 10.1007/s10840-015-0017-1
|View full text |Cite
|
Sign up to set email alerts
|

A low fibrillatory wave amplitude predicts sinus node dysfunction after catheter ablation in patients with persistent atrial fibrillation

Abstract: A low amplitude of the fibrillatory waves and a large LAVI were predictors of SND after restoration of sinus rhythm by ablation in patients with persistent AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In previous studies, several risk factors or predictors of SND after termination of AF have been reported, including older age, a female gender, a low preprocedural ventricular rate, and a large left atrium [ 24 , 28 , 29 , 30 , 31 , 32 ]. The present study found that age, female gender, and the underlying history of hypothyroidism were predictive of SND after AFL ablation.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, several risk factors or predictors of SND after termination of AF have been reported, including older age, a female gender, a low preprocedural ventricular rate, and a large left atrium [ 24 , 28 , 29 , 30 , 31 , 32 ]. The present study found that age, female gender, and the underlying history of hypothyroidism were predictive of SND after AFL ablation.…”
Section: Discussionmentioning
confidence: 99%
“…Bradycardia and sinus node dysfunction sometimes occur after persistent AF ablation, and bradycardia generally causes a decrease in cardiac output. 8 , 9 Accordingly, we hypothesized that cardiac output cannot be compensated for by a decrease in heart rate after the procedure, and that this is a causative factor in DHF. We investigated the association between heart rate and postprocedural DHF in patients undergoing AF ablation.…”
mentioning
confidence: 99%